Analisis Penerapan Akuntansi Persediaan Obat-obatan Berdasarkan PSAP No. 5 pada Kantor Puskesmas Purnama Kecamatan Pontianak Selatan - Dea, Medy Radea (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the application of Government Accounting Standard Statement (PSAP) No. 5 to medicine inventory accounting at the Purnama Community Health Center in South Pontianak. The study employs a descriptive qualitative approach, with data collected through interviews, observations, and document analysis. The analysis focuses on inventory classification, recognition, measurement, recording, valuation, and presentation in financial reports. The results indicate that the Purnama Community Health Center has appropriately implemented PSAP No. 5 in managing medicine inventories. Inventories are recognized when goods are received, measured at acquisition cost, recorded using stock cards and periodic physical counts, and valued using the First-In, First-Out method. The conformity assessment shows that all 12 indicators, or 100%, comply with PSAP No. 5. These findings demonstrate that the implementation of medicine inventory accounting supports transparency, accountability, and efficiency in public-sector financial management.